2002
DOI: 10.1007/bf02850270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a probiotic multivitamin compound on stress and exhaustion

Abstract: This 6-month study evaluated a probiotic multivitamin preparation in 42 adult men and women suffering from stress or exhaustion. The preparation was taken daily with breakfast. A psychological-neurologic questionnaire assessed psycho-organic, central vegetative, and somatic discomforts, and a validated list of adjectives was used to indicate the effect of therapy. At the end of the study, an overall 40.7% improvement in stress was noted, representing significant improvements of 17.4% in positive conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Oral supplementation with B. brevi and L. casei reduced the occurrence of NEC in premature infants [103]; this was likely due to the improvement in gastrointestinal motility. Administration of a probiotic multivitamin preparation was also found to significantly reduce the stress or exhaustion symptoms in healthy subjects [104]. Another major gastrointestinal disease targeted to test probiotic application is irritable bowel syndrome (IBS).…”
Section: Discussionmentioning
confidence: 99%
“…Oral supplementation with B. brevi and L. casei reduced the occurrence of NEC in premature infants [103]; this was likely due to the improvement in gastrointestinal motility. Administration of a probiotic multivitamin preparation was also found to significantly reduce the stress or exhaustion symptoms in healthy subjects [104]. Another major gastrointestinal disease targeted to test probiotic application is irritable bowel syndrome (IBS).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a combination of probiotic cultures and multivitamin/minerals has been shown to improve depressive symptoms in a group of fatigued adults under stress [148]. Chronic fatigue syndrome patients treated with Lactobacillus casei strain “Shirota” for two months showed a significant rise in both Lactobacillus and Bifidobacteria resulting in improved patient outcome [149].…”
Section: Future Emerging Areas For Probiotic Researchmentioning
confidence: 99%
“…Similarly in healthy human subjects, there was a decrease in HADS-A scores following ingestion over a 30 day period of formulation consisting of Lactobacillus helveticus and Bifidobacterium longum [24]. In a six-month study that looked at 42 subjects with stress and exhaustion, ingestion of a probiotic multivitamin led to an overall 40.7% improvement in stress [25]. Moreover, consumption of fermented foods that contain probiotics may have a protective effect against social anxiety symptoms in those at high genetic risk for social anxiety disorder [26].…”
Section: Discussionmentioning
confidence: 94%